Salmonella Effector SpvB Disrupts Intestinal Epithelial Barrier Integrity for Bacterial Translocation - Sun, Lanqing; Yang, Sidi; Deng, Qifeng; Dong, Kedi; Li, Yuanyuan; Wu, Shuyan; Huang, Rui (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonella are common enteric bacterial pathogens that infect both humans and animals. Intestinal epithelial barrier, formed by a single layer of epithelial cells and apical junctional complex (AJC), plays a crucial role in host defense against enteric pathogens to prevent bacterial translocation. However, the underlying mechanisms of intestinal epithelial barrier dysfunction caused by Salmonella are poorly understood. It is found that a locus termed Salmonella plasmid virulence (spv) gene exists extensively in clinically important Salmonella serovars. SpvB is a key effector encoded within this locus, and closely related to Salmonella pathogenicity such as interfering with autophagy and iron homeostasis. To investigate the interaction between SpvB and intestinal epithelial barrier and elucidate the underlying molecular mechanism, we used the typical foodborne disease agent Salmonella enterica serovar Typhimurium (Salmonella typhimurium) carrying spvB or not to construct infection models in vivo and in vitro. C57BL/6 mice were orally challenged with S. typhimurium wild-type strain SL1344 or spvB-deficient mutant strain SL1344-ΔspvB. Caco-2 cell monolayer model, as a widely used model to mimic the human intestinal epithelium in vitro, was infected with SL1344, SL1344-ΔspvB, or spvB complementary strain SL1344-c-ΔspvB, respectively. The results showed that SpvB enhanced bacterial pathogenicity during S. typhimurium infection in vivo, and contributed to intestinal epithelial barrier dysfunction in both infection systems. This SpvB-mediated barrier dysfunction was attributed to the cellular redistribution of Claudin-1, Occludin, and E-cadherin junctional proteins. Moreover, by using pharmacological inhibitors, we found that F-actin rearrangement and suppression of protein kinase C (PKC) signaling pathway were involved in SpvB-mediated barrier dysfunction. In conclusion, the study reveals the contribution of Salmonella effector SpvB to the dysfunction of intestinal epithelial barrier integrity, which facilitates bacterial translocation via the paracellular route to promote Salmonella systemic dissemination. Our findings broaden the understanding of host–pathogen interactions in salmonellosis, and provide new strategies for the therapy in limiting bacterial dissemination during infection.